HAZ, a novel peptide with broad-spectrum antibacterial activity - Mohammad Alsaggar; Mohammad Al-Hazabreh; Yara Al Tall; Alaa Al-Tarawneh; Ruba S. Darweesh; Majed Masadeh (Elsevier, 2022)
Objective: The growing microbial resistance to antibiotics is a global public concern, which creates serious needs for newer antimicrobial agents. Antimicrobial peptides (AMPs) are increasingly exploited in drug development as therapeutic candidates. Here, we aimed to design and characterize a novel peptide with broad spectrum antimicrobial activity. Methods: Hybridization and sequence modification approaches were used to design the novel peptide, named HAZ, aiming at optimizing the physicochemical parameters involved in antimicrobial activity. Peptide activities were assessed alone or combined with different selected antibiotics against various sensitive and drug-resistant bacterial strains. In addition, the hemolysis and the cytotoxic activities of HAZ peptide were evaluated on human red blood cells and epithelial adenocarcinoma cells (A549), respectively. Results: HAZ peptide was sequentially modified to result in favored physicochemical parameters (helicity 95.24 %, hydrophobic ratio 47 %, and net charge of 8 + ). Functional assessment of HAZ revealed significant antimicrobial activity, with MIC values of 15 - 20 µM against tested bacterial strains. It also exhibited biofilm eradication activity at slightly higher concentrations. HAZ-antibiotics combinations exhibited a synergistic action mode that led to dramatic decrease in the MIC values for both HAZ peptide and the antibiotic. Such efficacy was accompanied with minimal hemolytic toxicity on human erythrocytes. Importantly, HAZ displayed promising anticancer activity against human lung cancer cells. Conclusion: Rationally-designed antimicrobial peptides offer promising alternatives to the current antibiotics for management of infectious diseases. HAZ peptide is a broad-spectrum AMP, and a promising candidate for antimicrobial and anticancer drug development.